A Stable Anti-Fouling Coating on PVDF Membrane Constructed of Polyphenol Tannic Acid, Polyethyleneimine and Metal Ion - Wu, Lili (Polymers (Basel), 2019)
A hydrophilic and anti-fouling coating layer was constructed on a polyvinylidene fluoride (PVDF) microfiltration membrane by a novel surface modification method. The pristine membrane was firstly coated by (3-chloropropyl) trimethoxysilane/polyethyleneimine and tannic acid. Then, the metal ion was induced on the coating layer to coordinate with tannic acid and polyethyleneimine, forming a more stable and hydrophilic coating on the surface. The membrane’s surface morphology and chemical element analysis showed that the Tannic acid/ polyethyleneimine (TA/PEI) coating layer was denser and had more stability after the addition of metal ions, and this may be due to the coordination bond formed between the TA/PEI coating and metal ions. The results of the water contact angle and pure water flux measurements showed that the hydrophilicity and wettability of the modified membranes were improved obviously after introducing the metal ion layers. The anti-fouling performance and stability of the modified membrane were also characterized by the underwater oil contact angle (OCA), the separation efficiency, and the contact angle variation value for before and after the rinsing experiment. The modified membrane showed obvious stability and antifouling. Moreover, the retention rate of some composite membranes could reach 99.6%.